Pemaknaan Teologis M. Fethullah Gülen tentang Relasi Agama dan Sains - Mutamakkin Billa (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2011)
The article discusses Gülen’s theological perspective on the relation between science and Islam, which becomes the platform of his educational movement—while within Islamic knowledge tradition (theology), this matter is still debated—mainly in terms of the position and relation between reason and revelation (wahy). Gülen is interested in defending the position of Islamic theology towards science and knowledge, which has so far—as he concluded—played a subordinate role. Religion and science, to Gülen, cannot be considered equal in Islam. Gülen asserts that Muslims have not so far developed yet the concept of knowledge in its true meaning, based on Islamic values and formulated mainly from the Qur’an and the Prophet Muhammad’s deeds. Moreover, Gülen emphasizes that the assumption of separation of revelation and reason, which has been understood so far, has been, in fact, a false supposition. The clash that should exist is, in fact, between the secular view and the religious one.